Genitourinary menopausal syndrome: the potential of estriol - V N Prilepskaya (IP Berlin A.V., 2018)
Genitourinary menopausal syndrome is estrogen-dependent age-related changes due to estrogen deficiency and affecting the urethra, bladder, vagina. As for the leading methods of treatment, the diseases include estrogen hormone therapy, among which estriol deserves attention in view of its specific features of the action on target organs and the absence of a proliferative effect on the endometrium and mammary glands.